2010
DOI: 10.1098/rspb.2009.1545
|View full text |Cite
|
Sign up to set email alerts
|

Ions first: Na+uptake shifts from the skin to the gills before O2uptake in developing rainbow trout,Oncorhynchus mykiss

Abstract: This is the first direct physiological evidence in support of the ionoregulatory hypothesis, challenging the long-held assumption that teleost gills develop initially for gas exchange. Resting unidirectional sodium (Na þ ) uptake and oxygen (O 2 ) uptake across the skin and gills were measured simultaneously in larval rainbow trout, Oncorhynchus mykiss, during development. In soft and hard water, Na þ uptake shifted to the gills by 15 and 16 days post-hatch (dph) while O 2 uptake took 50 -80% longer and shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 34 publications
10
73
0
Order By: Relevance
“…Although very little is known about the mechanisms and pathways of acid-base regulation in larval fishes, it is clear that they must be capable of acid-base homeostasis (Brauner 2009). Indeed, the early ontogenetic development of gills in larval fish may be more important in ionoregulation and maintaining acid-base balance than for oxygen delivery (Fu et al 2010). Similar to the egg stage, the 24-h LC50 for larval fish is generally above 10 000 ppm CO 2 for the few species tested to date (Kikkawa et al 2003;Ishimatsu et al 2008).…”
Section: Effects On Larvaementioning
confidence: 96%
“…Although very little is known about the mechanisms and pathways of acid-base regulation in larval fishes, it is clear that they must be capable of acid-base homeostasis (Brauner 2009). Indeed, the early ontogenetic development of gills in larval fish may be more important in ionoregulation and maintaining acid-base balance than for oxygen delivery (Fu et al 2010). Similar to the egg stage, the 24-h LC50 for larval fish is generally above 10 000 ppm CO 2 for the few species tested to date (Kikkawa et al 2003;Ishimatsu et al 2008).…”
Section: Effects On Larvaementioning
confidence: 96%
“…It has been suggested that the embryonic heart beat might primarily serve alternative functions such as nutrient transport and angiogenesis (Burggren, 2004), whereas the gills serve in ionoregulation (Fu et al, 2010). Alternatively, the absence of a cardiorespiratory response to hypoxia could be explained by a lack of chemosensory feedback at this life stage.…”
Section: Series I and Iimentioning
confidence: 99%
“…The first or 'traditional' divided chamber (Fig. 1A) was designed to separate the head and gills from the rest of the body in CYA fish (Fu et al, 2010) and the protocol was almost identical to those described in previous studies (Zimmer et al, 2014c;Zimmer and Wood, 2015). CYA trout (∼200 mg; 30 days post-hatch) were initially anaesthetized to stage 3 anesthesia (McFarland, 1959) using 0.1 g l −1 neutralized MS-222 with 0.05 g l −1 neutralized MS-222 used to maintain anesthesia in the chambers.…”
Section: Divided Chamber Designmentioning
confidence: 99%
“…In most mature freshwater fish, J Na,in and J amm occur primarily across the gills (Smith, 1929;Maetz and Garcia-Romeu, 1964;Cameron and Heisler, 1983;Wright and Wood, 1985;Smith et al, 2012;Zimmer et al, 2014a), although the skin, kidney, and gastrointestinal system play minor roles. However, in post-hatch larval fish, the gills are underdeveloped and the skin ( primarily that overlying the yolk sac) represents the dominant site for both J Na,in and J amm (Esaki et al, 2007;Shih et al, 2008;Fu et al, 2010;Zimmer et al, 2014c).…”
Section: Introductionmentioning
confidence: 99%